If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 = y + -7 Reorder the terms: -5 = -7 + y Solving -5 = -7 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. -5 + -1y = -7 + y + -1y Combine like terms: y + -1y = 0 -5 + -1y = -7 + 0 -5 + -1y = -7 Add '5' to each side of the equation. -5 + 5 + -1y = -7 + 5 Combine like terms: -5 + 5 = 0 0 + -1y = -7 + 5 -1y = -7 + 5 Combine like terms: -7 + 5 = -2 -1y = -2 Divide each side by '-1'. y = 2 Simplifying y = 2
| abc=C*C | | 8(1.5)+2-4(1.5)=6+(1.5)-10 | | -612x=-108 | | 9-6(x+5)=2/3(6-3/2x) | | 2x/5=x+14/3 | | 3.4+x/2.5=4.6 | | -9(x-2)-21=-3 | | 2+-1x=20+5x | | -x+7(x+8)=6x-(3x+1) | | 4n-3(n-2)=6n-5 | | 2x^2+8x+32= | | -18=9u | | 3x-5x+9=-21 | | 4y+22=2(2v-3) | | 4x+2x+12=18 | | 7x+6=7x-6 | | -12y=-24 | | -9+8+6d+7d= | | 0=y-2x | | 6x-16=8x-34 | | (11b-11)/5=(3b-2)/2 | | 5x-11+6=-20 | | 65=5v | | 6x-18=8x-34 | | 9x+5=-94 | | 10/7+1/2t=7 | | 2y+-3=-2y+13 | | 6p^2+10p-36= | | 3(x-0.2)+.1x=5.6 | | x^2+4x+y^2-8y+10=0 | | 4b-8=2b+16 | | (4x-1)+(3x+1)+(x+4)=12 |